Evaluation of distribution system losses due to load unbalance - Ochoa, Luis F. [UNESP]; Ciric, Rade M.; Padilha-Feltrin, A. [UNESP]; Harrison, Gareth P. (My University, 2005)
Distribution network losses can vary significantly depending on the load unbalance. Here, an analysis of distribution system losses is presented that considers load unbalance and the effect of explicitly represented neutral wire. A general power flow algorithm for three-phase four-wire radial distribution networks, based on the current summation backward-forward technique is applied. Loss analysis results obtained from three-phase four-wire medium and low voltage test feeders with unbalanced load scenarios are presented and discussed considering: a) original phase and neutral wires resistances; and b) resistances obtained by performing Kron's reduction.
Keywords: Distribution networks; Load unbalance; Losses; Power flow; Three-phase four-wire